a) ĐK: \(\left\{{}\begin{matrix}x\ge0\\x\ne1\end{matrix}\right.\)
b) \(A=\dfrac{x+1-2\sqrt{x}}{\sqrt{x}-1}+\dfrac{x+\sqrt{x}}{\sqrt{x}+1}=\dfrac{\left(\sqrt{x}-1\right)^2}{\sqrt{x}-1}+\dfrac{\sqrt{x}\left(\sqrt{x}+1\right)}{\sqrt{x}+1}=\sqrt{x}-1+\sqrt{x}=2\sqrt{x}-1\)c) Ta có A<-1\(\Leftrightarrow2\sqrt{x}-1< -1\Leftrightarrow2\sqrt{x}< 0\Leftrightarrow\sqrt{x}< 0\left(ktm\right)\)
Vậy không có giá trị của x để A<-1
a.ĐK:
\(\left\{{}\begin{matrix}\sqrt{x}-1\ne0\\\sqrt{x}+1\ne0\\\sqrt{x}xđ\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x\ge0\\x\ne1\end{matrix}\right.\)
b.\(A=\sqrt{x}-1+\sqrt{x}=2\sqrt{x}.\)
c.Có :\(2\sqrt{x}\ge0\) nên không có giá trị nào của x để A<-1.
b.\(A=\dfrac{\left(\sqrt{x}-1\right)^2}{\sqrt{x}-1}+\dfrac{\sqrt{x}\left(\sqrt{x}+1\right)}{\sqrt{x}+1}=\sqrt{x}-1+\sqrt{x}=2\sqrt{x}-1\)
c.\(2\sqrt{x}-1\ge-1\)\(\Rightarrow A\ge-1\)
A=-1\(\Leftrightarrow x=0\left(TM\right).\)